Improved Tribological Properties of Poly(methyl methacrylate) Based Composites by the Synergistic Effect of Incorporating Ultra-High Molecular Weight Polyethylene and Heat Treatment - Gu, Dapeng; Wang, Shuaibing; Zhang, Jingchao; Liu, Ke; Chen, Suwen; Chen, Xiaofan; Wang, Zibo; Liu, Jintu (Journal of materials engineering and performance, 2022)
Poly(methyl methacrylate) (PMMA)-based composites filled with ultra-high molecular weight polyethylene (UHMWPE) were prepared. The synergistic effect of filling UHMWPE and heat treatment on the tribological properties of PMMA based composites was investigated by a ball-on-disk tribometer. Fourier Transform Infrared (FTIR) spectroscopy, Thermogravimetric Analysis (TG), and Field-Emission Scanning Electron Microscopy (FE-SEM) were used to characterize PMMA-based composites. It is shown that the friction coefficient and wear rate of PMMA based composite are reduced significantly by the combination of filling UHMWPE and heat treatment. The friction and wear performances of 20wt.% UHMWPE/PMMA composite with heat treatment are optimal. Compared with neat PMMA, the friction coefficient and wear rate reduce, respectively, about 70 and 85% by the synergistic effect of 20wt.% UHMWPE filling and heat treatment. The friction reduction is due to the lubrication of filling UHMWPE. The improvement of wear resistance is due to the improvement of the shore hardness and a more compacted microstructure, which is caused by heat treatment. Serious adhesive wear is the predominant wear mechanism of neat PMMA. The main wear mechanisms for UHMWPE/PMMA composites are slight adhesive wear and abrasive wear.